Investigative Interview of Indonesian Police Investigator - Rio Adhikara (IHSA Institute, 2022)
This research objective was to examine the investigative interview process of Indonesia police investigator. Interviews performed by South Tangerang Police CID investigator were analyzed using the Griffiths Question Map and five steps of PEACE model. Samples were obtained in two different cases –white collar crime and violence against woman. The results showed that the investigators managed to used appropriate questions well and perform an information-gathering approach in most of the interview. However, in a certain condition, a multiple question and accusatorial approach may also occured to get a more valuable information. Implications for research and practice include the limitation due to the absence of police interview records.